Analisis Prosedur Pelaksanaan Annual Servis Alat-Alat Keselamatan dan Alat Pemadam Kebakaran di Atas Kapal Sesuai Standar SOLAS - Hati, Angie Kusuma; Setiono, Beni Agus; Purwiyanto, Didik (Universitas Hang Tuah, 2023)
The role of shipping safety in the maritime transportation system is an absolute thing to be taken into account, because it involves the transportation of goods and people across the ocean which is full of danger and the threat of storms, fog and movements of the sea, shallowing and fixed and changing shipping sea routes, making sea transportation in high-risk shipping. Therefore, shipping safety must be truly guaranteed. This research aims to find out the procedures for implementing annual servicing of safety equipment, to find out the effects that occur on safety equipment and fire extinguishers on ships that comply with SOLAS standards. The research method used in writing this research uses the direct observation research method of an object carried out at PT. Salam Pacific Indonesia Lines. The data used is primary data obtained directly from sources and data collected by researchers from employees of PT. Salam Pacific Indonesia Lines and recorded. Primary data can be obtained by conducting interviews, secondary data can be obtained from documents about safety equipment and direct observation at the research site at PT. Salam Pacific Indonesia Lines. The results of the research can be concluded that it is important to maintain safety on board the ship to anticipate danger or accidents so it is necessary to prepare safety items along with valid certificates so that they can be used. Therefore, the safety equipment on board the ship has a big influence on the smooth operation of the ship.